Glutamine supplementation did not benefit athletes during short-term weight reduction - Finn, K. J.; Lund, R.; Rosene-Treadwell, M. (Journal of Sports Science & Medicine, 2003)
The purpose was to determine if glutamine supplementation would prevent a loss of lean mass in athletes during a 12-day weight reduction program. It was hypothesized that supplementation would spare lean body mass. Subjects (n=18) exercised and dieted to create a 4186kJ·day-1 energy deficit and a 8372 kJ·day-1 energy deficit on days 1-5, days 6-12, respectively. The glutamine (GLN) group (n=9) ingested 0.35 g·kg-1 body mass of glutamine while a placebo was administered to the remaining subjects. Body mass (BM), lean body mass (LBM) and fat mass (FM), were measured at days 0, 6, and 12. GLN and placebo groups both lost significant amounts of BM, LBM and FM. There were no significant differences between groups. The findings indicate little benefit for retention of lean mass with supplementation of glutamine during a short-term weight reduction program.